2018
DOI: 10.1038/s41598-018-32448-5
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between transgenerational acquired resistance and global DNA methylation in Arabidopsis

Abstract: Progeny of heavily diseased plants develop transgenerational acquired resistance (TAR). In Arabidopsis, TAR can be transmitted over one stress-free generation. Although DNA methylation has been implicated in the regulation of TAR, the relationship between TAR and global DNA methylation remains unknown. Here, we characterised the methylome of TAR-expressing Arabidopsis at different generations after disease exposure. Global clustering of cytosine methylation revealed TAR-related patterns in the F3 generation, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 63 publications
2
66
0
Order By: Relevance
“…Since then, various studies have confirmed that DNA methylation is inversely correlated with basal resistance to biotrophic pathogens and responsiveness/expression of SA-dependent genes (81,84,155). Furthermore, independent groups have reported that infection of Arabidopsis with Pseudomonas syringae alters genome-wide DNA methylation (44,106,128).…”
Section: Epigenetics: What's In a Name?mentioning
confidence: 97%
See 3 more Smart Citations
“…Since then, various studies have confirmed that DNA methylation is inversely correlated with basal resistance to biotrophic pathogens and responsiveness/expression of SA-dependent genes (81,84,155). Furthermore, independent groups have reported that infection of Arabidopsis with Pseudomonas syringae alters genome-wide DNA methylation (44,106,128).…”
Section: Epigenetics: What's In a Name?mentioning
confidence: 97%
“…Hence, DNA demethylation is essential for the elicitation, transmission, and/or expression of TAR. Another recent study revealed that TAR in Arabidopsis is associated with global shifts in DNA methylation at CG contexts in gene bodies, which were more pronounced after three generations than one generation of disease stress (128). However, the genes carrying these differentially methylated cytosines (DMCs) were not enriched for defense-related functions and there was little overlap in DMCs between independent experiments.…”
Section: Py57ch23_tonmentioning
confidence: 99%
See 2 more Smart Citations
“…2007; Jiang et al . 2014; Stassen et al . 2018), climate-CG methylation associations most likely represent solid adaptive signals.…”
Section: Introductionmentioning
confidence: 99%